Neuroticism, Fear of Missing Out, and Phubbing on Teenager Girls who Used Social Media - Nur Evira Anggrainy; Zulkifli Mansyur; Sri Seprianto Maddusa (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2023)
The research aimed to investigate the influence of personality trait neuroticism and fear of missing out on phubbing behavior among female teenage social media users in Manado City. The study involved 337 participants who completed three questionnaires – The Big Five Personality Inventory (BFI), Generic Scale of Phubbing (GSP), and Fear of Missing Out Scales. The results showed that the neuroticism personality trait had a significant positive effect on phubbing, with a significance value of 0.000. Similarly, fear of missing out had a positive and significant influence on phubbing, with a significance value of 0.000. Overall, the study provides insights into the relationship between personality traits and phubbing behavior among teenage girls who use social media. The implication of this research are to improve the quality of interaction on teenager girls who used social media can be provide with intervention to reduce the fear of missing out.